Hot-wire arc additive manufacturing of aluminum alloy with reduced porosity and high deposition rate. (1st February 2021) - Fu, Rui; Tang, Shuiyuan; Lu, Jiping; Cui, Yinan; Li, Zixiang; Zhang, Haorui; Xu, Tianqiu; Chen, Zhuo; Liu, Changmeng
Abstract: Wire arc additive manufacturing (WAAM) technology has attracted considerable interest in large-scale metallic components, but porosity and low deposition rate are the two dominating technical challenges in WAAM of aluminum alloy. In order to effectively solve these problems, a novel method of hot-wire arc additive manufacturing is used to fabricate aluminum alloy. Systematic studies are carried out to investigate the formation mechanism of the pores, the macro/microstructures, as well as the mechanical properties of the parts. It is found that the pores were mainly clustered at the inter-layer. With the increase of the hot-wire current, the porosity firstly decreases, then reaches a minimum at 100 A, and afterwards increases progressively. The corresponding density changes from 96.8% at the hot-wire current of 0 A to 99.6% at 100 A. Increasing the current from 0 A to 120 A also leads to the increase of the deposition rate by about 3.5 times, and the gradual increase of the size of equiaxed grain by 1.6 times. The mechanical properties are considerably improved with the decrease of the porosity. Graphical abstract: Unlabelled Image Highlights: A novel hot-wire arc additive manufacturing was used to manufacture aluminum alloy. The effect of hot-wire current on porosity was studied. The deposition efficiency of aluminum alloy was greatly improved. Parts with excellent mechanical properties were obtained.